Darwinizing cough and its modern triggers: newer management approach to cough associated with allergy, asthma, upper airway cough syndrome - Vora, Agam; Tiwaskar, Mangesh; Juvekar, Meenesh; Gupta, Sailesh; Biswas, Ayndrila; Bhole, Milind; Deshpande, Swapnil (International Journal of Research in Medical Sciences, 2024)
Cough is a crucial defensive reflex of the respiratory system, essential for expelling irritants and secretions. It can present as acute or chronic cough, often exacerbated by allergic conditions such as allergic rhinitis (AR) and upper airway cough syndrome (UACS). Effective management of cough focuses on addressing the underlying aetiology while simultaneously offering symptomatic relief. Fixed-dose combinations (FDCs) are becoming an increasingly effective approach to enhance patient adherence and streamline treatment. Non-sedating antihistamines, like Bilastine, have demonstrated efficacy in alleviating AR and associated cough, making them an ideal choice for cough syrup formulations. The combination of Bilastine with Dextromethorphan and Phenylephrine provides a suitable treatment option for cough related including UACS, asthma, and respiratory allergies. This formulation is particularly well-suited for pediatric patients aged six and older, offering effective relief from throat irritation without sedation, being well-tolerated, and minimizing risks of cardiovascular and hepatotoxic effects. Pulmonologist, Otolaryngologist, Physician and paediatrician opinions have been gathered to review current practices and provide insights into effective management strategies. This review delves into the pathophysiology and clinical significance of cough, particularly in relation to respiratory allergies, highlighting its complexities and the need for ongoing research to refine treatment strategies and improve patient outcomes.